Floristic and ethnic perspective on wild forest plant species of Nongkhyllem Reserve Forest, Nongpoh, Meghalaya, India (Asian Journal of Ethnobiology, 2021)
Abstract. Parkash V. 2021. Floristic and ethnic perspective on wild forest plant species of Nongkhyllem Reserve Forest, Nongpoh, Meghalaya, India. Asian J Ethnobiol 4: 93-105. This paper elucidates the indigenous traditional knowledge of wild plants usage by Khasi people (ethnic group) of Nongkhyllem Reserve Forest, Nongpoh, Meghalaya, India. About 117 different wild forest plant species belonging to 63 families were collected and enumerated for their traditional usage. Most of the plant parts utilized were of herbs (44) followed by trees (32) and shrubs (28). The climbers (7) and scrubs (6) have been utilized least in traditional usage by Khasi people in Nongkhyllem Reserve Forest. It is interesting to mention that due to overexploitation, some plant species, i.e., Abroma augusta L., Phlogacanthus thyrsiflorus (Roxb.), Puereria tuberosa L., Eryngium foetidum L., Nees, Smilax aspera L. and Houttuynia cordata Thunb. were utilized in colossal quantity, and these plant species are nearing their threshold and hence, are under threat. Only two plants of A. augusta L. were found around forest edge areas of reserve forest, so there is a need of the hour to conserve this plant species in situ and ex-situ conditions. This study emphasizes research potentials and the need to document traditional knowledge about wild forest plant species utilization to benefit society and humankind through scientific intervention.
Keywords: Diversity, Floristics, Indigenous traditional knowledge, Traditional usage